Living in the age of airplanes [videorecording (DVD)] - Ford, Harrison, 1942-; Terwilliger, Brian J.; Terwilliger, Brian J. (National Geographic, 2016)
"LIVING IN THE AGE OF AIRPLANES is a story about how the airplane has changed the world. Filmed in 18 countries across all 7 continents, it renews our appreciation for one of the most extraordinary and awe-inspiring aspects of the modern world."--Container.